That special someone: When the board views its chair as a resource - Krause, Ryan; Semadeni, Matthew; Withers, Michael C. (Strategic management journal, 2016)
Research summary: Many boards view their chairs as valuable resources. We predict that whether a board adopts such a view depends on the board chair's human and social capital. Data from S&P 500 firms suggest that while a board chair's human capital increases the probability that the board views him or her as a resource, social capital has no overall effect. In a post-hoc investigation, however, we find the board chair's independence to be an important boundary condition for the effect of social capital. With this exploratory research, we aim to spur research devoted specifically to board chairs. Such research will become increasingly important over time as firms continue to separate their CEO and board chair positions. Managerial summary: The purpose of this research was to determine the factors that lead a board of directors to view its chair as a valuable resource. We expected that board chairs with high human and social capital would be more likely to be viewed as a resource by their colleagues. Surprisingly, only human capital exhibited such an effect overall. Social capital increases the likelihood a chair is viewed as a resource when the chair is independent, but actually decreases the likelihood a chair is viewed as a resource when the chair is either the current or former CEO. These results suggest that boards generally value human capital in their chairs, but view social capital through a somewhat more complex lens. We explore the possible implications of these findings in the article.